Comparative genomic insight into the myxobacterial carbohydrate-degrading potential - Saraf, Niharika; Sharma, Gaurav (Frontiers in Microbiology, 2025)
Myxobacteria are an intriguing group of social-behavior-depicting microbes with unique physiological characteristics such as fruiting body formation, gliding motility, and predation, encompassing the largest genomes (>9 Mb) within the Eubacteria kingdom. These soil-dwelling organisms are crucial for lignocellulosic biomass degradation, which has both ecological and industrial significance. While previous studies have demonstrated polysaccharide deconstruction abilities in a few myxobacterial species, we aim to elucidate the distribution of their Carbohydrate Active Enzymes (CAZymes) domains per organism, with a focus on proteins involved in the catabolism of critical polysaccharides such as cellulose, lignin, xylan, starch, pectin, fructan, chitin, and dextran, across 61 high-quality sequenced myxobacterial genomes. Our findings reveal that 3.5% of the total genes at the median level have domains related to CAZyme functions across different myxobacterial families. Notably, family Archangiaceae (4.4%) and Myxococcaceae (3.7%) members exhibit the most significant genomic diversity and potential for degrading multiple substrates within lignocellulosic biomass. These plentiful CAZymes probably enable these majorly soil-harboring myxobacteria to breakdown various carbohydrate substrates into simpler biological molecules, which not only allow these organisms to sustain in poor-nutrient environments but also enable them to be critical players in carbon cycling and organic matter decomposition. Overall, it can be postulated that myxobacteria have an unexplored genomic potential that may play an integral role in the degradation of recalcitrant plant biomass, potentially influencing soil health and composition. This study further suggests the critical ecological importance of these CAZymes in sustaining the balance of terrestrial ecosystems and diverse industrial applications.